PENGARUH MODAL KERJA DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - lda Firdaus; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the effect of working capital ang capitar structure on profitability in food and beverage sub-sector companies on the Indonesian Stock Exchange. In this atudy using quantitative descriptive data types. The data source used is secondary data using financial statement data food and baverage sub-sector companies listed on the Indonesia Stock Exchange from 2015-2019 period using the purposive sampling method. Thi study uses 6 companies as samples. Data were analyzed using multiple linear regression with the help of SPSS software. Besides that, the data noemality test and classica assumption tsest were also carried out. Based on the results of the t-test conducted, it shows that working capital has no effect on profitability ang capital structure has an effects profitability. And the f-test results show that simultaneously working capital and capital structure affect the profitability of food and baverage companies listed on the IDX. With an R Square value of 0.329, it means that 32,9 % of profitability is influenced by working capital and capital structure, while the rest is influenced by oter variables. Keywords: Working Capital, Capital Stucture, Profitability